Knowledge and Attitude of Refractive Error Correction Methods in Patients Visiting Eye Hospital - Subedi, Anup; Basnet, Gyan Bahadur; Baral, Nabin; Parajuli, Anil; Belbase, Umesh (Nepalese Journal of Ophthalmology, 2024)
Introduction: There are different types of refractive error correction methods that are either appropriate or appealing to all patients. Although spectacles appear to be the most common method of visual correction, there is no single method preferred for correction that is accepted by all patients. Knowledge and attitude towards methods of correction may influence the preferred method of correction.Objective: To determine the knowledge and attitude of patients towards refractive error correction methods.Methodology: This analytical cross-sectional study included 150 subjects aged ≥18 years who visited the refraction unit of Himalaya Eye Hospital. They were randomly interviewed using structured questionnaires which consisted of open- and closed-ended questions to gather information on demography, knowledge, and attitude towards different eye care practitioners as well as spectacles, contact lens, and refractive surgery for correcting refractive error and analysed using descriptive statistics for frequency and Chi-square test for analysing association between variables.Result: Out of 150 participants, Majority of the participants had history of ocular examination.  Only 67 (44.7%) participants had history of using spectacles, whereas 33 (22%) participants knew about the contact lens and 21 (14%) participants were aware about the refractive surgery as a method of refractive correction. Lack of information and fear of side effects were the major reasons for not using contact lens and refractive surgery as a method of refractive error correction.Conclusion: The knowledge and perception about the refractive error correction methods, especially for contact lens and refractive surgery, was low among the participants.